Exosomes: Potential Therapies for Disease via Regulating TLRs - Hong-Yan Guo; An-Chun Cheng; Ming-Shu Wang; Zhong-Qiong Yin; Ren-Yong Jia (Mediators of Inflammation)
Exosomes are small membrane vesicles that retain various substances such as proteins, nucleic acids, and small RNAs. Exosomes play crucial roles in many physiological and pathological processes, including innate immunity. Innate immunity is an important process that protects the organism through activating pattern recognition receptors (PRRs), which then can induce inflammatory factors to resist pathogen invasion. Toll-like receptor (TLR) is one member of PRRs and is important in pathogen clearance and nervous disease development. Although exosomes and TLRs are two independent materials, abundant evidences imply exosomes can regulate innate immunity through integrating with TLRs. Herein, we review the most recent data regarding exosome regulation of TLR pathways. Specifically, exosome-containing materials can regulate TLR pathways through the interaction with TLRs. This is a new strategy regulating immunity to resist pathogens and therapy diseases, which provide a potential method to cure diseases.